Челюсти - гроза округи: Секреты настоящей рыбалки: Повесть / Э. Веркин - Веркин Эдуард (Книжки для мальчишек, 2004)
Экземпляры: (20180828) / Инвентарный номер: 41046 / Цена: 78.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: В 31 / ББК: 84(2Рос=Рус)6